Localized Intra-Cavitary Therapy to Drive Systemic Anti-Tumor Immunity - Donnenberg, Vera S.; Wagner, Patrick L.; Luketich, James D.; Bartlett, David L.; Donnenberg, Albert D. (Frontiers in Immunology, 2022)
Metastasis to the pleural and peritoneal cavities is a common terminal pathway for a wide variety of cancers. This article explores how these unique environments both promote aggressive tumor behavior and suppresses anti-tumor immunity, and ways in which local delivery of protein therapeutics can leverage the contained nature of these spaces to a therapeutic advantage, achieving high intra-cavital concentrations while minimizing systemic toxicity.